Usefulness of a multifunctional snare designed for colorectal hybrid endoscopic submucosal dissection (with video) - Ohata, Ken (Endosc Int Open, 2018)
Since colorectal endoscopic submucosal dissection (ESD) remains technically difficult, hybrid ESD was developed as an alternative therapeutic option to achieve en bloc resection of relatively large lesions. In this feasibility study, we evaluated the safety and efficacy of hybrid colorectal ESD using a newly developed multifunctional snare. From June to August 2016, we prospectively enrolled 10 consecutive patients with non-pedunculated intramucosal colorectal tumors 20 – 30 mm in diameter. All of the hybrid ESD steps were performed using the “SOUTEN” snare. The knob-shaped tip attached to the loop top helps to stabilize the needle-knife, making it less likely to slip during circumferential incision and enables partial submucosal dissection. All of the lesions were curatively resected by hybrid ESD, with a short mean procedure time (16.1 ± 4.8 minutes). The mean diameters of the resected specimens and tumors were 30.5 ± 4.9 and 26.0 ± 3.5 mm, respectively. No perforations occurred, while delayed bleeding occurred in 1 patient. In conclusion, hybrid ESD using a multifunctional snare enables easy, safe, and cost-effective resection of relatively large colorectal tumors to be achieved. Study registration: UMIN000022545